History of Hoogere Kweekschool Purworejo-Bandung (1914-1931) - Dimas Nurillah Setianingrum; H.Y. Agus Murdiyastomo (Sriwijaya University in collaboration with Perkumpulan Program Studi Pendidikan Sejarah Se-Indonesia (P3SI) dan Masyarakat Sejarawan Indonesia (MSI)., 2023)
Indonesia has a number of colonial educational buildings scattered in various regions. On the island of Java, there are many teaching schools that produce intellectual, artistic and political figures. Teacher schools have become one of the granaries for producing great Indonesian figures. This study aims to determine the actions of Hoogere Kweekschool as a teacher school in creating great figures in each of their careers. This study uses historical research methods in the form of heuristics, source criticism, interpretation and historiography based on qualitative data analysis. The results of the study stated that Hoogere Kweekschool (H.K.S) was first established in 1914 in Purworejo. The students come from the best graduates of all Kweekschools in the Dutch East Indies. H.K.S graduates are usually directly placed in either H.I.S or Schakelschool. In 1921 the H.K.S student association was formed called